2018
DOI: 10.18502/kss.v3i10.3466
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure, Corporate Governance and Dividend Policy: Evidence from Indonesia

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…On the other hand, institutional investors may prefer to get their income dividends to be invested properly according to their investment policies. This result is consistent with (Benjamin et al, 2016;Ibrahim & Shuaibu, 2016;Le & Le, 2017;Mehdi et al, 2017;Thanatawee, 2013;Ullah et al, 2012) and in contrast (Berezinets et al, 2017;Kouki & Guizani, 2009;Mardani & Indrawati, 2018;Reyna, 2017) who found that a higher institutional ownership leads to lower dividend payments.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, institutional investors may prefer to get their income dividends to be invested properly according to their investment policies. This result is consistent with (Benjamin et al, 2016;Ibrahim & Shuaibu, 2016;Le & Le, 2017;Mehdi et al, 2017;Thanatawee, 2013;Ullah et al, 2012) and in contrast (Berezinets et al, 2017;Kouki & Guizani, 2009;Mardani & Indrawati, 2018;Reyna, 2017) who found that a higher institutional ownership leads to lower dividend payments.…”
Section: Discussionsupporting
confidence: 87%
“…Dapat disimpulkan bahwa kepemilikan manajerial berpengaruh positif dan signifikan terhadap kebijakan dividen. Pernyataan tersebut sejalan dengan penelitian yang dilakukan oleh Moin et al (2019), Jayanti & Puspitasari (2017), Mardani et al (2018), Sumartha (2016, Pebrianti (2018), Balamuralikrishnan & Gnanasekar (2019), Badejo & Hamza (2019).…”
Section: Tabel 4 Uji Koefisien Determinasiunclassified
“…Bank size assessed using the log of overall assets can also be employed as proxy for the prices of external debt financing. A rather direct and positive connection is actually anticipated between size as well as dividend payout since bigger companies face lower issuing costs (Malavia Mardani & Khusniyah Indrawati, 2018). The variability in capital design and structure suggests that bank's potential to have better access to capital markets, since banks will have the ability to swap between equity and debt and then take advantage of lower transaction costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Guyot, et al, 2014) Dividend payout ratio is positively related to the fraction of ownership of external shareholders in the bank, since external shareholders demand more dividends. If the external shareholders proportion of ownership is actually much less than internal ownership, then agency expense is actually reduced and the bank pays lower dividends (Malavia Mardani & Khusniyah Indrawati, 2018). Stability of cash flows in the bank may be related to dividend payout.…”
Section: Literature Reviewmentioning
confidence: 99%